The Theoretical Foundations of Contextual Interpretation of the Qur’an in Islamic Theological Schools and Philosophical Sufism - Halim Calis (Religions, 2022)
Contextual interpretation of the Qur’an has grown in popularity with the rise of Islamic modernism, mostly because of the need to reform Islamic thought and institutions. Although Qur’anic contextualism is a modern concept, this study argues that its theoretical origins can be traced back to classical Islamic scholarship. Most of the Islamic theological schools, as well as the Akbarī School (the school of Ibn al-‘Arabī), a prominent representative of philosophical Sufism, acknowledged the contextuality of the Qur’an by distinguishing between transcendent divine speech and its limited manifestation in human language. Furthermore, Shams al-Dīn al-Fanārī of the Akbarī School developed a hermeneutical theory in which he questioned the authority and the nature of Qur’anic exegesis and emphasized the idea that the Qur’anic text can have multiple meanings, due to the multiplicity of perceptions in different human contexts. I propose that, of the thinking in pre-modern Islamic scholarship, Akbarian scriptural hermeneutics best accommodates the modern practice of reading the Qur’an contextually.